POTENSI STASIUN KERETA API CIMAHI SEBAGAI LANDMARK KOTA CIMAHI - Ramaniya Amanta, Nadindra; N. Sunartio, Anindhita (Riset Arsitektur (RISA), 2024)
Abstract - Cimahi is known as a Military City with various historical legacies, especially from the era of Dutch colonialism. One of the Dutch colonial era legacies in Cimahi is the Cimahi Train Station (SKAC). SKAC has the potential to become a landmark of Cimahi based on its supportive historical context, unique function, and role for the city. Cimahi itself does not yet have a city identity or landmark that can represent its history and Military City image. With the potential of SKAC as a landmark for Cimahi, it is necessary to identify and explore the requirements of the city landmark's elements based on the criteria, characteristics, and types of landmark found in SKAC. Cimahi needs a city landmark because it requires an identity that represents its image as a Military City and a reference point or a landmark for human direction and location. This research used a qualitative descriptive approach with a historical research methodology to identify the criteria, characteristics, and types of landmark. The research was conducted at SKAC, located at Jl. Stasion No. 1, Baros Village, Cimahi Tengah District, Cimahi, West Java. This study identified landmark criteria according to Kevin Lynch's theory and landmark characteristics according to Donald Appleyard's theory at SKAC. The criteria and characteristics of landmarks were identified based on parameters and indicators from the researcher's observation, field observation, and literature review. Then, identifying the type of landmark according to Havva Alkan Balla's theory based on the researcher's perception and collective memory and the people of Cimahi. The results of this study indicate that SKAC has the potential to become a landmark of Cimahi. Additionally, SKAC falls into the landmark types of city memory-historical, daily life/city usage, and personal memory, supported by research in the form of interviews with Cimahi residents. These findings show that SKAC has an important role in the development of Cimahi and is worthy of becoming an icon or landmark of Cimahi. Keywords: Urban Landmark, Dutch Indich Colonial Building, Heritage Building, Railway Station Cimahi